Prevalence and Factors associated with Peripheral Neuropathies among Patients with Diabetes attending Jinja Regional Referral Hospital: A Retrospective open cohort study. - Violet Alimwenda (Student's Journal of Health Research, 2022)
Aim: To determine the prevalence and factors associated with diabetic peripheral neuropathy among diabetic patients of Jinja Regional Referral Hospital.  Methodology: A retrospective open cohort study was conducted among 1000 diagnosed diabetic patients ofJRRH. Data on the socio-demographics, age, duration of symptoms, smoking, alcohol intake, HIV status, BMI, cholesterol levels, history of kidney disease, heart or brain problems, and footing problems were analyzed using multiple logistic regression. A p-value of ˂0.05 was considered significant. Results: The study revealed that the mean age of developing DPN was 51.1.674 (67.4%) of the patients obtained from the register were females and 324 (32.4%) were male.760 (76%) of the patients obtained from the register were of average BMI of 24 and 160 (16%) had a BMI of more than 25.540(54%) of the patients developed diabetic neuropathy while 460(46%) of the patients did not develop DNP. The factors associated with DPN were brain or heart problems X2=22.97, Eye problems X2=20.934, P=0.001, Kidney problems X2=22.97, P=0.001, High cholesterol X2=19.153, P=0.001, Alcohol intake X2= 35.224, P=0.001 and Adequate physical activity X2=1.349, P=0.001. Conclusion: The Prevalence of DPN was high (54%) and occurs in 1 in every 6 DM patients in Jinja Regional Referral Hospital among patients with diabetes. The factors associated with diabetic neuropathy among diabetic patients are; age, BMI, physical activities, sex, and underlying conditions like brain or heart problems, kidney problems, eye problems, and high cholesterol levels. Recommendations: Early diagnosis of DM with regular sugar monitoring would play a significant role in identifying these problems.